Guest Editor’s Introduction: Culture and Causal Chains of Care—A Perspective on the Chronology of Health and Medical Communication in Cross-Cultural Contexts - St.Amant, Kirk (Journal of Technical Writing and Communication, 2020)
Today, diseases can spread internationally faster and farther than ever before, and a range of public health issues can “go global” quickly and easily. The challenge becomes communicating ideas of care—that is, issues of health and wellness—across different cultures, languages, and geopolitical contexts. Doing so involves understanding the dynamics of such factors and how to apply this knowledge effectively. The entries in this special issue examine such factors and provide readers with frameworks for understanding and strategies for addressing these issues.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDQ3MjgxNjIwOTA2MTI5